Hypoxia-induced miR-210 modulates inflammatory response and fibrosis upon acute peripheral ischemia. (25th November 2020) - Zaccagnini, G; Greco, S; Longo, M; Maimone, B; Voellenkle, C; Fuschi, P; Carrara, M; Creo, P; Maselli, D; Spinetti, G; Tirone, M; Mazzone, M; et al.
Abstract: Introduction: We previously demonstrated in mouse models of peripheral and heart ischemia that miR-210 is necessary and sufficient to stimulate blood perfusion recovery, as well as arteriolar and capillary density increase following ischemic damage. Aim: To clarify the role of inflammatory cells in miR-210-induced angiogenesis. Methods and results: In a mouse model of acute limb ischemia, miR-210 loss-of-function was obtained by administration of complementary anti-miR-210 LNA oligonucleotides (anti-210), while doxycycline-inducible miR-210 transgenic mice (Tg210) were used for gain-of-function experiments. Transcriptomic and gene ontology analysis in ischemic gastrocnemius muscles upon miR-210 blocking displayed an enrichment of categories related not only to angiogenesis, but also to inflammation, suggesting that miR-210 decrease prompted a pro-inflammatory and anti-regenerative response. Accordingly, immunofluorescence staining of ischemic muscles of anti-210 treated mice, showed an increased presence of granulocytes (Scr = 28±7, anti-210 = 108±17 cells/mm 2, p<0.001), T and B lymphocytes (Scr = 32±8 SE, anti-210 = 112±19 cells/mm 2, p<0.003; Scr = 45±10, anti-210 = 103±14 cells/mm 2, p<0.006, respectively) and macrophages (Scr = 17±1, anti-210 = 27±4 cells/mm 2 ; p<0.03), with a higher M1/M2 macrophage ratio (Scr = 0.6±0.1, anti-210 = 1.7±0.3; p<0.02). Conversely macrophages (WT = 17±2, Tg210 = 5±1 cells/mm 2, p<0.003) and M1/M2 ratio (WT = 1.0±0.1, Tg210 = 0.3±0.1, p<0.02) were decreased in ischemic TG-210 mice. To clarify the role of inflammatory cells in miR-210-induced angiogenesis, bone-marrow (BM) transplantation experiments were performed. Tg210 mice transplanted with WT BM cells (BM-wt/R-Tg210), compared with WT mice transplanted with Tg210 BM (BM-Tg210/R-wt) showed increased blood perfusion (vascularity ratio: BM-wt/R-Tg210 = 0.8±0.1, BM-Tg210/R-wt = 0.6±0.1; p<0.01) and capillary density after ischemia (BM-wt/R-Tg210 = 497±41, BM-Tg210/R-wt = 212±32 cap./mm 2 ; P<0.00001). Thus, miR-210 expression in the muscle and not in the BM-derived cells was crucial for miR-210-stimulated angiogenesis. Interestingly, BM-wt/R-Tg210 mice also showed increased fibrotic areas (sirius red staining: BM-wt/R-Tg210 = 12±2, BM-Tg210/R-wt = 22±3 A.U.; p<0.01), characterized by α-SMA+, vimentin+ and collagen V+ stainings. Fibrotic regions were enriched in cells double-positive for both CD206/α-SMA and CD45/α-SMA, as well as in phospho-Smad3+ cells, suggesting the activation of the TGFβ pathway. In vitro experiments showed higher expression of α-SMA and collagens in TG-210 BM-derived macrophages compared to WT, both in the presence and in the absence of TGFβ (α-SMA: w/o TGFβ 2.3±1.4 fold increase p<0.004; TGFβ+ 11.3±2 fold increase p<0.003). Conclusions: Collectively, these data show that a miR-210 enriched milieu was sufficient to improve angiogenesis after ischemia. Moreover, a context-dependent regulation by miR-210 of the inflammatory response and of fibrosis were identified. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Italian Ministry of health: Ricerca Corrente and 5X1000